“The character of the missionary” Evangelization, legitimation, and mysticism in the Chinese rural world during the dynastic change from Ming to Qing - Martínez Esquivel, Ricardo (2024)
During the economic and sociopolitical crises due to the dynastic change from Ming to Qing, paradoxically the Catholic mission had its greatest progression among the worlds of dialects and illiteracy of rural Chinese space. A hypothesis that allows us to understand this new dynamic in the missionary enterprise could be found in the “character of the missionary”, an image of a degree of symbolic legitimacy for all spheres of Chinese culture of the time. That is, from his clothing, his haircut, his liturgical way of expressing himself and even his ability to direct the rituals, the presence and leadership of the religious imposed an aura of power, fear, and respect among the population masses. In this way, the missionary consecrated himself as one of the Mystical masters of the supernatural in late imperial China of the Ming.